Polyphenol supplementation and antioxidant status in athletes: A narrative review - Bojarczuk, A.; Dzitkowska-Zabielska, M. (Nutrients, 2023)
Antioxidants in sports exercise training remain a debated research topic. Plant-derived polyphenol supplements are frequently used by athletes to reduce the negative effects of exercise-induced oxidative stress, accelerate the recovery of muscular function, and enhance performance. These processes can be efficiently modulated by antioxidant supplementation. The existing literature has failed to provide unequivocal evidence that dietary polyphenols should be promoted specifically among athletes. This narrative review summarizes the current knowledge regarding polyphenols` bioavailability, their role in exercise-induced oxidative stress, antioxidant status, and supplementation strategies in athletes. Overall, we draw attention to the paucity of available evidence suggesting that most antioxidant substances are beneficial to athletes. Additional research is necessary to reveal more fully their impact on exercise-induced oxidative stress and athletes` antioxidant status, as well as optimal dosing methods.